Feasibility Study of Atmospheric Water Harvesting by Direct Cooling in Thailand - Munsin, Ronnachart; Yeunyongkul, Pracha; Nuntapap, Nawee; Panya, Jirasak; Promdan, Surapin; Kesai, Sawat; Kumwan, Rawat; Narkpakdee, Jeerawich; Wannachai, Autanan; Sirasakamol, Orasa; Jantanasakulwong, Kittisak; Chungcharoen, Thatchapol; et al. (Journal of Technical Education Science, 2023)
The objective of this work is to assess the potential of the atmospheric water harvesting (AWH) by direct cooling under the climate of Thailand. The assessment was considered from water scarcity, meteorological data and engineering analysis, including moisture harvesting index (MHI), water capability and energy cost. The meteorological data between 2012-2021 were used as primary data for engineering analysis. The results showed that Thailand has the potential to supply freshwater by using AWH with direct cooling. The average MHI of Thailand is 0.548 which is comparable with high potential of global assessment. 71 cities from 77 cities in Thailand have MHI over 0.50, which is the favorable condition for AWH by direct cooling. From the calculation under Thailand conditions, the water harvesting rates by direct cooling could be in the range of 0.97-1.30 L/h with energy costs as low as 0.047 USD/L for 71 cities in Thailand.